Developing physics problem-solving skill test for grade X students of senior high school - Amipa Tri Yanti Nadapdap; Edi Istiyono (REID (Research and Evaluation in Education), 2017)
This research aimed to develop a physics problem-solving skill (PSS) test for grade X students of senior high school which met test instrument characteristics and feasibility. The development stages included: (a) test designing, (b) test trial, and (c) test revision and preparation. The designing stage included: (1) needs analysis, (2) mapping, (3) drawing conclusion, (4) determining test purpose, (5) determining competencies, (6) determining materials, (7) preparing answers, (8) writing items, (9) validating content, (10) improving and preparing the test, and (11) preparing the scoring guide with PCM. The trial stage consisted of: (1) determining trial subjects, (2) performing trial, and (3) analyzing trial result data based on IRT. The study was performed in Kulonprogo involving 281 students. The result shows that the instrument fulfills content validity with Aiken’s V of 0.95 to 0.98. Based on INFIT MNSQ criteria, 52 items fit PCM, item difficulty index ranges from -1.47 to 0.88, meaning that all items are good, and information function analysis and SEM show that the test  fits the ability between -1.3 and 2.7. Therefore, the test instrument meets the characteristics and feasibility to measure physics PSS in high school.